An efficient and novel method to screen Botrytis cinerea resistance genes based on TRV-induced gene silencing with lily petal discs. (November 2022) - Xiang, Jun; Lei, Xin; Wu, Ze; Cao, Xing; Zhang, Dehua; Teng, Nianjun
Abstract: Lily ( Lilium spp.) is an important ornamental crop because of its colorful flowers and fragrant smell. However, gray mold often occurs on lily flowers and leaves, which causes extensive economic losses. Most lily cultivars have poor tolerance to gray mold and are difficult to resist Botrytis cinerea, so it is urgent to identify resistance genes for developing resistant cultivars. So far, only a few B. cinerea resistant genes in lilies have been identified. This study aims to build an efficient method to screen B. cinerea resistance genes in lily. The resistance determination of detached lily discs revealed that the petal discs were more sensitive to B. cinerea than the leaves, and 'Sorbonne' was a suitable experimental material with B. cinerea pathogen susceptibility for investigation. In addition, it was also found that the petal discs from the completely opened 'Sorbonne' flowers were inoculated with B. cinerea spore suspension at 1 × 10 5 concentrations, which was more appropriate for symptom observation. Based on these results, we developed an Agrobacterium -mediated tobacco rattle virus (TRV)-induced gene silencing (VIGS) method on detached 'Sorbonne' petal discs for screening B. cinerea- resistance genes. The bacteria solution at an OD600 of 1.5 got the highest VIGS efficiency at 9 days post infection. Three differently expressed genes, LlWRKY3, LlWRKY7, and LlWRKY10, which came from the B. cinerea -infection transcriptome, were identified with this TRV-based VIGS method. Silencing of them in petal discs caused them to be more sensitive to B. cinerea . In the current study, the VIGS method based on TRV was successfully developed on detached 'Sorbonne' petal discs. Target genes of petal discs that were vacuum infiltrated with Agrobacterium bacteria solution at an OD600 of 1.5 were silenced well after 9 days. Compared with traditional method of screening resistant gene, the TRV-VIGS method with petal discs was a convenient and efficient method for screening B. cinerea resistant genes, and have important value in breeding of lily with high resistance to gray mold. Highlights: The completely opened flowers of 'Sorbonne' are suitable for B. cinerea symptom observation. The Agrobacterium concentration at an OD600 of 1.5 is optimal for efficient VIGS on 'Sorbonne' petal discs. The TRV-VIGS method with petal discs was a convenient and efficient method for screening B. cinerea resistant genes. LlWRKY3, LlWRKY7, and LlWRKY10 may be B. cinerea resistant genes .